Exosome Protein Diversity is Greater in Preterm Milk than Term Milk - Kraft, Jamie (Université d'Ottawa / University of Ottawa, 2019)
Infants born prematurely are a vulnerable population with diverse nutritional needs to battle their increased risk of gastrointestinal (GI) diseases. Human milk is considered the 'gold standard' of infant nutrition. Human milk not only provides nutrition for newborn growth, but contains bioactive components which contribute to GI maturation, immune protection and neurological development. Among these bioactive components are extracellular vesicles known as exosomes. Exosomes are double-lipid membrane vesicles containing mRNA, microRNA and proteins, secreted by cells as a form of cell-to-cell communication. Human milk exosomes contain immune-related microRNA and proteins that withstand in vitro simulated human digestion, suggesting that signals are being delivered to the cells residing in the GI tract of a newborn. In premature birth, disruption of GI tract maturation predisposes the infant to increased susceptibility of GI inflammatory diseases. To prevent inflammation, immune tolerance in the GI tract of premature infants should be promoted and I hypothesized that exosomes differ between preterm and term milk, and may contribute to the anti-inflammatory effects of human milk. Human milk exosomes from mothers who gave birth to term or preterm infants were characterized based on size, surface protein markers and total protein. Preterm milk exosomes contained a more diverse protein profile. The effects of milk exosomes on intestinal epithelial cells were observed in an in vitro model using Caco-2/15 cells. Milk exosomes were able to attenuate the inflammatory response induced by heat-killed bacteria as measured by the transcription of pro-inflammatory cytokines.
Keywords: Human milk; Exosomes; Term milk; Preterm milk; Proteomics; Inflammation; Gastrointestinal epithelium